Antibacterial and anti-phytopathogenic substances from the insect pathogenic fungus Gibellula sp. BCC36964. (June 2015) - Bunbamrung, Nantiya; Intaraudom, Chakapong; Supothina, Sumalee; Komwijit, Somjit; Pittayakhajonwut, Pattama
Graphical abstract: Highlights: Four new compounds were isolated from insect fungus, Gibellula sp. BCC36964. The compounds were evaluated for antibacterial and anti-phytopathogenic activities. New dibenzo[1, 4]dioxins exhibited anti- Bacillus cereus with MICs values 1.56–6.25 μg/mL. Abstract: Four new compounds (1 –4 ), which were (−)-( 7R )-7- O -methylsydonic acid, gibellulic acid, gibellulins A and B, together with 14 known compounds (5 –17 and orcinol) were isolated from the insect pathogenic fungus, Gibellula sp. BCC36964. The chemical structures were elucidated by employing NMR spectroscopic techniques, physico-chemical data, and chemical method. These compounds were evaluated for the biological activities including anti-bacterial, anti-phytopathogenic, anti- Herpes simplex virus-type 1 activities, and cytotoxicity against both cancerous (MCF-7, KB, NCI-H187) and non-cancerous (Vero) cells.